Global COVID-19 vaccine acceptance rate: a systematic review and meta-analysis. - Alimohamadi, Yousef; Hosamirudsari, Hadiseh; Hesari, Elahe; Sepandi, Mojtaba (Journal of Public Health: From Theory to Practice (2198-1833), 2023)
Aim: Achieving high COVID-19 vaccination coverage rates is essential as soon as a vaccine is available to deal with and end this pandemic. Due to the different amounts of COVID-19 vaccine acceptance rates in different regions, the pooled estimation of this rate is essential. Therefore, we conducted a systematic review and meta-analysis to investigate worldwide COVID-19 vaccine acceptance rates. Subject and methods: International databases (including, Web of sciences, PubMed, and Scopus) were searched to identify related studies. The heterogeneity among studies was assessed using the I index, the Cochran Q test, and T. A random-effects model was used to pool estimate vaccine acceptance rates. Results: The overall pooled estimate of COVID-19 vaccine acceptance rate was 65.1 (95% CI 60.1–70.1; P < 0.001, I = 99.8). The vaccine acceptance rate in the general population was 68.5 (95% CI 62.5–74.5; P < 0.001, I = 99.8) and among healthcare workers (HCWs) was 55.9 (95% CI 47.8–64.1; P < 0.001, I = 99.6). The lowest COVID-19 vaccine acceptance rate was in the Middle East (46.1% (35.1–57.0)), and the highest coverage rate was (85% (71–99.1)) in South America. Conclusion: COVID-19 vaccine acceptance rate among HCWs is lower than the general population. More studies are recommended to identify related factors to the COVID-19 vaccine acceptance rate.